RELIGIOUSITY AS AN ANTECEDENT OF EMPLOYEES’ ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - OPOKU MENSAH, ABIGAIL (Advances in Social Sciences Research Journal, 2016)
Organisational practitioners and academics have recognized that employees’ discretionary behaviours that go beyond their formally prescribed roles hold great promise for organizations and their members. This calls for identification of individual and organizational factors that promote these behaviours. The study investigated the extent to which employees’ level of religiosity predicts their organizational citizenship behaviour. A cross-sectional survey was conducted involving 272 which comprised of 125 males (46%) and 147 females (54%) and were conveniently sampled from various organizations in the Central region of Ghana. Sixty-four percent of the respondents were Christians, while 34.3% and 1.7% were Muslims and Traditionalists respectively. Religiousity was measured using Huber and Huber’s five dimension Centrality of Religion Scale (CRS), and OCB was measured using Organizational Citizenship Behavior Checklist (OCB-C) developed by Fox and Spector’s which has a total of 20 items. The data were analyzed using descriptive statistics, independent samples t-test, Pearson’s Product Moment correlation, ANOVA and multiple regressions. The results indicated that religiosity of the employees had significant contribution to their citizenship behaviour in their organizations. Regression analysis of the dimension of the religiosity scale showed that only religious ideological values and private practice significantly contributed to the OCB of the employees. ANOVA analysis also indicated that the religious denominations of the employees significantly influenced their OCB. The findings of this study suggest that efforts by organizations and society at large to inculcate religious values in employees would be invaluable for smooth and efficient organizational functioning. Further implications are discussed.